Manifestations of Quaternary syn‐eruptive fluid circulations on carbonate veins, Central Anatolian Volcanic Province. (4th November 2020) - Karabacak, Volkan; Mutlu, Halim; Deniz, Kiymet
ABSTRACT: In this study, we investigate the geochronological, geochemical and isotopic characteristics of two travertine sites surrounded by Quaternary eruption centres in central Anatolia with ample palaeo‐eruption records. High‐resolution carbonate precipitation records, revealed by U‐Th dating, are clustered around 5–35, 60–100 and 120–170 ka and are well correlated with the dataset on eruptions as well as the position of fractures related to the volcanic centres. Syn‐eruptive carbonate precipitation seems to occur due to the circulation of CO2 ‐rich fluids along the extensional fracture systems aligned tangentially to the related volcanic conduit and, therefore, the study of this system could be an alternative technique for the reconstruction of palaeo‐eruptions. δ 18 O values of the studied travertines are within the range of meteogene fluids. Oxygen isotope compositions at around 130 ka match well with Glacial Termination II that is also recorded by climate proxies in various cave and benthic deposits throughout the world. It is likely that the studied carbonates were precipitated under similar fluid circulation conditions which are represented by a high rate of dilatation followed by a meteoric water influx into the extensional fractures.